2013
DOI: 10.1017/s0954422412000212
|View full text |Cite
|
Sign up to set email alerts
|

Zinc, pancreatic islet cell function and diabetes: new insights into an old story

Abstract: Zn is an essential trace element, involved in many different cellular processes. A relationship between Zn, pancreatic function and diabetes was suggested almost 70 years ago. To emphasise the importance of Zn in biology, the history of Zn research in the field of diabetes along with a general description of Zn transporter families will be reviewed. The paper will then focus on the effects of Zn on pancreatic b-cell function, including insulin synthesis and secretion, Zn signalling in the pancreatic islet, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 114 publications
1
67
0
12
Order By: Relevance
“…249 ZraP has been shown to bind zinc, 250 and a metalloproteomic study demonstrated that in zinc excess conditions, the large majority of cellular zinc in E. coli was bound to ZraP. 251 The catalytic molecular chaperone activity of ZraP is Zn-dependent, and Zn also affects its oligomerisation state, with higher oligomers (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) observed in the presence of zinc. A structure for ZraP from Salmonella typhimurium is available, but without bound Zn (pdb 3lay; Fig.…”
Section: View Article Onlinementioning
confidence: 99%
“…249 ZraP has been shown to bind zinc, 250 and a metalloproteomic study demonstrated that in zinc excess conditions, the large majority of cellular zinc in E. coli was bound to ZraP. 251 The catalytic molecular chaperone activity of ZraP is Zn-dependent, and Zn also affects its oligomerisation state, with higher oligomers (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) observed in the presence of zinc. A structure for ZraP from Salmonella typhimurium is available, but without bound Zn (pdb 3lay; Fig.…”
Section: View Article Onlinementioning
confidence: 99%
“…Copper, zinc, and selenium are cofactors of antioxidant enzymes such as superoxide dismutase and glutathione peroxidase and therefore play a pivotal role in the mechanism of cellular antioxidant defense [8]. Zinc has a pivotal role in the antioxidant system and also takes part in the synthesis, storage, and release of insulin [9]. The lower zinc levels have been associated with insulin resistance and chronic inflammation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc dyshomeostasis was associated with Alzheimer's disease and altered deposition of extracellular amyloid-b plaques (Craddock et al 2012). Decreased zinc content was also described in post-mortem pancreata of diabetic individuals over 75 years ago (Scott and Fisher 1938), and the role of this metal ion in insulin secretion and glucose homeostasis was confirmed since then by several reports (Chimienti 2013;Sladek et al 2007). Airways inflammation, one of the main hallmarks of asthma, has also been associated with deregulated zinc homeostasis (Zalewski et al 2005).…”
Section: Introductionmentioning
confidence: 94%